Pengaruh Motivasi dan Disiplin Kerja Terhadap Produktivitas Karyawan pada PT. PLN (Persero) UP3 Bontang di Kota Bontang - Icha Nur Octarina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to test simultaneously, partially, and to find out which is the dominant influence between motivation and work discipline variables on employee productivity at PT. PLN (Persero) UP3 Bontang in Bontang City. This type of research is quantitative using a sample of 47 respondents by collecting primary data through interviews and questionnaires, secondary data by searching for literature in the form of journals and books related to the variables to be studied. The research results show that the variables of motivation and work discipline have a simultaneous and partial effect on productivity and the motivation variable is the most dominant variable that has an effect on employee productivity at PT. PLN (Persero) UP3 Bontang in Bontang City.